3D Rotational Angiography in Follow-Up of Clipped Intracranial Aneurysms. (20th January 2014) - Kumar, Subhash; Gaikwad, Shailesh B.; Mishra, Nalini Kant
Abstract : Introduction . 3D Rotational Angiography (RA) is indispensable for evaluation of intracranial aneurysms, providing infinite viewing angles and defining the aneurysm morphology. Its role in follow-up of clipped aneurysms remains unclear. We aimed to compare the aneurysm residue/recurrence detection rate of 3D RA with 2D digital subtraction angiography (DSA). Methods . 47 patients harboring 54 clipped aneurysms underwent both 2D DSA and 3D RA. The residual/recurrent aneurysms were classified into five grades and the images of both modalities were compared. Results . The residual/recurrent aneurysm detection rate was 53.70% (29/54 aneurysms) with 2D DSA and 66.67% (36/54 aneurysms) with 3D RA (P = 0.05 ). In 12 aneurysms, 3D RA upgraded the residue/recurrence among which nine had been completely not detected on 2D DSA and were found to have grade one or two residual necks on the 3D RA, and, in three cases, a small neck on 2D DSA turned out to be aneurysm sac on 3D RA. In a total of 5 aneurysms, the classification was downgraded by 3D RA. Conclusion . 3D RA picks up more aneurysm residue/recurrence; hence, both 2D DSA and 3D RA should be performed in follow-up evaluation of clipped aneurysms.